Spatial variation in risk and consequence of Batrachochytrium salamandrivorans introduction in the USA - Richgels, Katherine L. D.; Russell, Robin E.; Adams, Michael J.; White, C. LeAnn; Grant, Evan H. Campbell (Royal Society open science, 2016)
A newly identified fungal pathogen, Batrachochytrium salamandrivorans(Bsal), is responsible for mass mortality events and severe population declines in European salamanders. The eastern USA has the highest diversity of salamanders in the world and the introduction of this pathogen is likely to be devastating. Although data are inevitably limited for new pathogens, disease-risk assessments use best available data to inform management decisions. Using characteristics of Bsalecology, spatial data on imports and pet trade establishments, and salamander species diversity, we identify high-risk areas with both a high likelihood of introduction and severe consequences for local salamanders. We predict that the Pacific coast, southern Appalachian Mountains and mid-Atlantic regions will have the highest relative risk from Bsal. Management of invasive pathogens becomes difficult once they are established in wildlife populations; therefore, import restrictions to limit pathogen introduction and early detection through surveillance of high-risk areas are priorities for preventing the next crisis for North American salamanders.